New bio-based sustainable polymers and polymer composites based on methacrylate derivatives of furfural, solketal and lactic acid - Raynold Techie-Menson; Charles K. Rono; Anita Etale; Gift Mehlana; James Darkwa; Banothile C.E. Makhubela (Elsevier, 2023)
Monomers derived from renewable sources are of great interest to drive sustainable polymer chemistry. Herein, bio-based furfural, glycerol and lactic acid were used as building blocks to prepare methacrylate monomers via simple transesterification reactions in high yield and purity. The monomers were polymerized and co-polymerized by employing a free radical solution polymerization technique using 1,1-azobis cyclohexanecarbonitrile (ABCN) initiator. The resultant new co-polymers (P(FAMA-co-SoMA), P(FAMA-co-LAMA) and P(SoMA-co-LAMA)) were obtained in high yields and proved to have sizeable molecular weights (Mw from 2540 to 29395 g mol-1 and Mn from 2194 to 7463 gmol-1). Thermogravimetric analysis and differential scanning calorimetry (DSC) measurements on these polymers revealed good thermal properties (thermal stability ranging between 125 °C and 155 °C) with some crystalline regions identified by DCS and PXRD. The polymers were reinforced using cellulose triacetate and polysulfone to give new polymer composites (Psf/PFAMA, Psf/PFAMA-co-SoMA, Psf/PSoMA, CTA/PFAMA, CTA/PFAMA-co-SoMA, CTA/PSoMA), which were amorphous and degraded hydrolytically (in acidic and basic aqueous solutions) by up to 10% in just 24 h. The polymer composites were fashioned into thin films and membranes and applied preliminarily as coatings and water filtration membranes.